The Role of Digital Leadership and Digital Capabilities on Dynamic Capabilities and Digital Performance of MSME Employees - Muh. Afdal Abdullah; Rahmad Sholing Hamid; Duriani (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study explores the role of digital leadership and digital capabilities in improving employee dynamic capabilities and employee digital performance in the micro, small, and medium enterprise (MSME) sector in Indonesia. With an integrative approach, this study tests the relationship between these variables using a theoretical model based on quantitative methods. The results of the study show that digital leadership has a significant influence in creating an adaptive and collaborative work culture, while employee digital capabilities increase innovation and productivity. Employee dynamic capabilities were found to be a key mediator that strengthens the relationship between digital capabilities and employee digital performance. This study provides theoretical contributions by integrating these variables in the context of MSMEs and offers practical implications for MSME leaders in optimizing digital technology for business sustainability in the era of digital transformation. This study also underlines the need for strategic policies and training that support digitalization to improve the competitiveness of MSMEs.